Public Information Openness Strategy in Maintaining Quality and Accountability of 2024 Elections in Banten Province - Hilman Hilman; Pri Utami (International Journal of Social Service and Research (IJSSR), 2023)
The 2024 Simultaneous Election is a Democratic process that has been mutually agreed upon by the Government and the People's Representative Council. This process certainly does not only bring about constitutional consequences but also legal certainty which has implications for all stakeholders in the central, provincial and district/city governments in Indonesia. Accountability from election organizers, namely the General Election Commission (KPU) and the Election Supervisory Body (Bawaslu) in all stages is very important, because the stages and results determination process are expected not to cause conflict between election participants and their sympathizers. Then the quality of elections also needs to get serious attention, this quality is also related to the professionalism of election organizers, so to answer these two demands there needs to be information disclosure as stated in law number 14 of 2008 concerning public information transparency. Banten Province can run simultaneous elections in 2024 if the KPU and Bawaslu work in a professional and accountable manner from all stages. Election quality in Banten province can be achieved if the organizers know and implement the current regulations. Leadership Commitment, Collaboration with all stakeholders, and carrying out various innovations to convey Periodic information, immediately, and information at any time about the implementation of the 2024 Election must be carried out by the KPU and Bawaslu of Banten Province. Commitment, Collaboration and Innovation in the holding of elections in Banten province are novelties in this research. democratic, honest, fair, transparent and the results can be accounted for.